2002
DOI: 10.19182/remvt.9846
|View full text |Cite
|
Sign up to set email alerts
|

Epidémiologie de la tuberculose et de la brucellose des bovins en zone périurbaine d'Abéché (Tchad)

Abstract: Cette étude a eu pour objectif de préciser l’épidémiologie de la tuberculose et de la brucellose des bovins dans le bassin laitier d’Abéché (préfecture du Ouaddaï, Tchad oriental). La population étudiée a été constituée d’animaux de plus d’un an pour la tuberculose et de femelles de plus d’un an pour la brucellose. L’échantillon a été sélectionné à l’aide d’un sondage à deux degrés (village puis éleveur). Le diagnostic a été réalisé par intradermotuberculination (simple puis comparative) pour la tuberculose et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
6
14
0
1
Order By: Relevance
“…Those are RVF, Q fever, and brucellosis. The National Surveillance Network for Animal Diseases (REPIMAT) is not currently monitoring these diseases, and very few studies were carried out in the last two decades in the country (Massenet et al 1993, Delafosse et al 2002, Durand et al 2003, Ringot et al 2003, Schelling et al 2003. Our study showed serological evidence of these pathogens in the study area, especially RVF where the situation seems to be endemic, contrary to the expected status of an epidemic disease that occurs after heavy rainfall.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Those are RVF, Q fever, and brucellosis. The National Surveillance Network for Animal Diseases (REPIMAT) is not currently monitoring these diseases, and very few studies were carried out in the last two decades in the country (Massenet et al 1993, Delafosse et al 2002, Durand et al 2003, Ringot et al 2003, Schelling et al 2003. Our study showed serological evidence of these pathogens in the study area, especially RVF where the situation seems to be endemic, contrary to the expected status of an epidemic disease that occurs after heavy rainfall.…”
Section: Discussionmentioning
confidence: 48%
“…The main risk factors identified for brucellosis were the ethnic Arabic group herding by the children of the herdsmen. (Delafosse et al 2002). A confirmed case of Brucella melitensis with Plasmodium falciparum coinfection was reported in a young veterinary researcher returning to France from Chad after working in close contact with farmers and their animals for more than 3 months in 2004 (Badiaga et al 2005).…”
Section: Brucellosismentioning
confidence: 95%
“…244 13 245 (Schelling et al, 2004) 15 2000 Probabilistic TRB, TFC 2.6% ± 1.2% Sedentary herds in Abéché peri-urban area, producing milk for local market. (Delafosse et al, 2002) 2008-09 Unknown 7% National level reported in OIE questionnaire (Akakpo et al, 2009) 2014 Unknown TRB 5.7% (95% C.I. : 3.8-7.6%) South-eastern shore of Chad (only the islands, not the mainland) (Abakar et al, 2014) iELISA 11.9% (95% C.I.…”
Section: General Overviewmentioning
confidence: 99%
“…The significant difference observed between results of RB and iELISA tests was previously reported by several authors in Benin and elsewhere in Africa (Delafosse et al, 2002;Kouamo et al, 2010;Dean et al, 2013;Sanogo et al, 2013). The monthly variations of the prevalence are due to variations of the antibody titre.…”
Section: Discussionmentioning
confidence: 57%